117k views
12 votes
Factorise :
(x+6)•(x+2)=0
[This is a quadratic equation]​

2 Answers

1 vote

Answer:

x = -6

x = -2

Explanation:

Finding the zeros :

  • (x + 6)(x + 2) = 0

By this, we understand that if either of the factors equals 0, then the expression's value will also be 0.

  • x + 6 = 0 ⇒ x = -6
  • x + 2 = 0 ⇒ x = -2

Solution :

  1. x = -6
  2. x = -2
User Yassine Younes
by
4.7k points
4 votes
  • (x+6)(x+2)=0
  • x(x+2)+6(x+2)=0
  • x²+2x+6x+12=0
  • x²+8x+12=0

The zeros are

  • x=-6 and -2
User Max Pevsner
by
5.2k points